27=4(u+3)-7u

Simple and best practice solution for 27=4(u+3)-7u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=4(u+3)-7u equation:



27=4(u+3)-7u
We move all terms to the left:
27-(4(u+3)-7u)=0
We calculate terms in parentheses: -(4(u+3)-7u), so:
4(u+3)-7u
We add all the numbers together, and all the variables
-7u+4(u+3)
We multiply parentheses
-7u+4u+12
We add all the numbers together, and all the variables
-3u+12
Back to the equation:
-(-3u+12)
We get rid of parentheses
3u-12+27=0
We add all the numbers together, and all the variables
3u+15=0
We move all terms containing u to the left, all other terms to the right
3u=-15
u=-15/3
u=-5

See similar equations:

| 1+8(3-4n)=-31-4n | | 2x+100-x=6x-7 | | 45y=9= | | -28=2x+8=5x | | 6x-(x=3)=4(2x+3)-3 | | 58=(5x-7) | | -5(w-2)=2w+31 | | 30n=3+6 | | -3(8b-2)+5(6b+6)=-4b+4b | | 15x-23=15-+12 | | 4(20x+75=1,260 | | -3x+12=-9(x-4) | | 16t^2=79 | | -5(x+2)=-4(x+4) | | 4x-3(x+3)=3/5(5x+3)-10 | | 10n+4=86 | | 3x-5(x-4)=-6+2x+14 | | 2u+47=7(u+6) | | 8+3(3k-4)=-1+3(k+7) | | 4.4=(x)11 | | 4.4=xx11 | | 5x=80-(1÷2) | | 6(y+3)=-2(3y+9) | | 45c-9=5c+7+66c | | 19=4h=1-h | | 43+y+57=180 | | 100x-200=50x-75 | | 2(k+7)+8(k-7)=4k-2-2k | | 4x^-64=17 | | x2-x=56 | | 19=q4+15 | | 3{x+1}=33 |

Equations solver categories